Influence of the joint treatment with granulocyte colony-stimulating factor and drugs elevating extracellular adenosine on erythropoietic recovery following 5-fluorouracil-induced haematotoxicity in mice - Weiterová, L; Hofer, M; Pospísil, M; Znojil, V; Vácha, J; Vacek, A; Pipalová, I (European journal of haematology, 2000)
The presented data address the problem of pleiotropic effects of granulocyte colony-stimulating factor (G-CSF) and suggest the ability of drugs increasing the level of extracellular adenosine to activate erythropoiesis when given jointly with G-CSF. To demonstrate these interactions, the effects of the drugs on the recovery from erythropoietic damage induced in mice by a single dose of 5-fluorouracil (5-FU) were investigated. Elevation of extracellular adenosine and thus activation of adenosine receptors was induced by joint administration of dipyridamole (DP), a drug inhibiting the cellular uptake of adenosine, and adenosine monophosphate (AMP), an adenosine prodrug. The drugs were injected in a 4-d treatment regimen starting 2 h after 5-FU injection. Both DP+AMP and G-CSF alone induced only weak effects. However, the combination of the three drugs produced significant elevation of erythrocytes in the peripheral blood which pertained in the posttreatment period. Stimulation of proliferation of erythroid progenitor cells (BFU-E) in femoral bone marrow and increased levels of reticulocytes in the peripheral blood were observed in the course of the 4-d treatment regimen. In addition, significantly decreased mean cell haemoglobin accompanying the elevated numbers of erythrocytes in the combination-treated mice was found. This effect could be interpreted as the result of a sublethal 5-FU-induced damage to erythroid progenitor and precursor cells forced to proliferate intensively by the combination therapy. The observed additivity and synergism of G-CSF with elevated extracellular adenosine in terms of erythropoiesis is an interesting finding with potential implications in clinical practice.
Keywords: retikulocyty; počet erytrocytů; Adenosine; erytropoéza; Erythroid Precursor Cells; fluoruracil; Erythrocytes; Reticulocytes; Dipyridamole; Hemoglobins; zvířata; myši; myši inbrední C57BL; časové faktory; faktor stimulující kolonie granulocytů; erytroidní prekurzorové buňky; Mice; Mice, Inbred CBA; Erythropoiesis; Phosphodiesterase Inhibitors; Adenosine Monophosphate; Male; inhibitory fosfodiesteras; dipyridamol; antimetabolity; Mice, Inbred C57BL; erytrocyty; Fluorouracil; Erythrocyte Count; Granulocyte Colony-Stimulating Factor; Animals; myši inbrední CBA; Antimetabolites; mužské pohlaví; adenosinmonofosfát; kombinovaná farmakoterapie; hemoglobiny; Time Factors; Drug Therapy, Combination; adenosin